2013
DOI: 10.1186/1742-6405-10-1
|View full text |Cite
|
Sign up to set email alerts
|

A new system for parallel drug screening against multiple-resistant HIV mutants based on lentiviral self-inactivating (SIN) vectors and multi-colour analyses

Abstract: BackgroundDespite progress in the development of combined antiretroviral therapies (cART), HIV infection remains a significant challenge for human health. Current problems of cART include multi-drug-resistant virus variants, long-term toxicity and enormous treatment costs. Therefore, the identification of novel effective drugs is urgently needed.MethodsWe developed a straightforward screening approach for simultaneously evaluating the sensitivity of multiple HIV gag-pol mutants to antiviral drugs in one assay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 13 publications
7
35
5
Order By: Relevance
“…On the other hand, the 27.8% prevalence of IPs detected among patients on HAART in this study is higher than that reported in Brazil (24%) and Dessie (17.6%) [ 19 , 24 ] but lower than from studies done in Indonesia (50%), in selected ART centers of Adama, Afar and Dire-Dawa (48%), Jimma (39.6%) and Addis Ababa (34.3%), [ 11 , 23 , 25 , 26 ]. This lower prevalence might be due to better laboratory test supported follow-up and better awareness of the patients themselves in adopting prevention and treatment measures against intestinal parasites in our study area plus the combined effect of anti-helminthes and HAART may better decrease occurrence of IPs.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, the 27.8% prevalence of IPs detected among patients on HAART in this study is higher than that reported in Brazil (24%) and Dessie (17.6%) [ 19 , 24 ] but lower than from studies done in Indonesia (50%), in selected ART centers of Adama, Afar and Dire-Dawa (48%), Jimma (39.6%) and Addis Ababa (34.3%), [ 11 , 23 , 25 , 26 ]. This lower prevalence might be due to better laboratory test supported follow-up and better awareness of the patients themselves in adopting prevention and treatment measures against intestinal parasites in our study area plus the combined effect of anti-helminthes and HAART may better decrease occurrence of IPs.…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of Strongyloides stercoralis is higher in non-HAART (6.9%) than patients on HAART (2.5%) in the present study which is comparable with a study done in Nigeria (6.39%) [ 6 ]. But higher than studies done in Malaysia (0%), China (0%) and Dessie (0.7%) [ 17 , 18 , 24 ]. The possible reasons might be due to geographical differences, comparatively small sample size in this study and age differences i.e.…”
Section: Discussionmentioning
confidence: 63%
“…A model system based on lentiviral vectors was used to study antiviral activity of fucoidans [16,22]. Pseudo-HIV-1 particles are recombinant lentiviruses based on HIV-1.…”
Section: Resultsmentioning
confidence: 99%
“…DNA of the lentiviral vector containing the marker eGFP gene and the plasmids directing the synthesis of the proteins that are required for the formation of pseudo-HIV-1 particles were introduced into HEK293 cells via calcium phosphate transfection. The pseudo-HIV-1 particles were collected 24 h following transfection with a 12 h interval [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation